Stabilization of calcareous subgrade soils with polyelectrolytes: mechanisms and mechanical properties. Issue 1 (6th December 2023) - Huang, Jianxin; Mohomad, Yosef; Kogbara, Reginald B.; Masad, Eyad; Sukhishvili, Svetlana; Little, Dallas
ABSTRACT: Organic polyelectrolytes, i.e. anionic poly(sodium 4-styrenesulphonate) (PSS), cationic poly(diallyldimethylammonium chloride) (PDADMAC) and their polyelectrolyte complexes (PECs) were evaluated for stabilisation of calcareous sandy subgrade soil. This paper investigated the effects of polymer type, surface charge type of PEC, concentrations of PEC solutions and dosages of polymer solutions added to the soil on improvement of soil mechanical properties. We found that anionic polymers, for both PECs and individual polyelectrolytes, were superior to their cationic counterparts in improving soil strength. Besides, the constituent polyelectrolytes, PSS and PDADMAC, worked better than their PECs for the specific soil investigated. The strength of polymer-treated soils was also found to increase with the increase in dosages of the polymer solutions as well as curing periods. Furthermore, polymer-treated soil specimens exhibited significant toughness improvement, which was higher than cement-treated samples. Scanning electron microscopy images revealed the abundance of long palygorskite fibres covering the surfaces of larger calcite and dolomite particles and linking surrounding aggregates after adding polymers. This observation suggests the interconnection of palygorskite fibres and their linking networks between and among coarse aggregates as the likely mechanism of polymer stabilisation of the soil studied.